Peran Advokat Dalam Memberikan Bantuan Hukum Berdasarkan Undang-Undang Nomor 16 Tahun 2011 Tentang Bantuan Hukum - Zahra Hayati; Khofifah Nabila; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The purpose of this research is to find out the role of advocates in providing legal assistance based on Law Number 16 of 2011 concerning Legal Aid, where this research uses the library research method, which can be concluded that the provision of legal aid by advocates besides aims to guarantee and fulfilling the rights of poor people or groups to get access to justice as well, but also aiming to ensure that legal aid is provided evenly throughout the territory of the Republic of Indonesia and to create an effective, efficient and accountable judiciary. Keywords: role of advocates, legal aid